2022
DOI: 10.3390/microorganisms10071383
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus salivarius UCC118™ Dampens Inflammation and Promotes Microbiota Recovery to Provide Therapeutic Benefit in a DSS-Induced Colitis Model

Abstract: The use of probiotics such as Lactobacillus and Bifidobacterium spp. as a therapeutic against inflammatory bowel disease (IBD) is of significant interest. Lactobacillus salivarus strain UCC118TM is a commensal that has been shown to possess probiotic properties in vitro and anti-infective properties in vivo. However, the usefulness of UCC118 TM as a therapeutic against colitis remains unclear. This study investigates the probiotic potential of Lactobacillus salivarius, UCC118™ in a mouse model of colitis. DSS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…L. salivarius alleviated inflammation and restored a balanced environment in a DSS-induced colitis model. 74 L. johnsonii has shown efficacy in reducing infection by the diplomonad Giardia intestinalis in gerbils and in inhibiting C. perfringens colonization in chickens. 75 , 76 Studies have indicated that the oral administration of L. delbrueckii regulates mucosal and systemic immune responses in mice with colitis.…”
Section: Resultsmentioning
confidence: 99%
“…L. salivarius alleviated inflammation and restored a balanced environment in a DSS-induced colitis model. 74 L. johnsonii has shown efficacy in reducing infection by the diplomonad Giardia intestinalis in gerbils and in inhibiting C. perfringens colonization in chickens. 75 , 76 Studies have indicated that the oral administration of L. delbrueckii regulates mucosal and systemic immune responses in mice with colitis.…”
Section: Resultsmentioning
confidence: 99%
“…Lacticaseibacillus rhamnosus PL60 supplementation increased signals of apoptosis, and uncoupling protein levels in adipose tissue, and serum leptin, which can contribute to reducing obesity. The administration of Ligilactobacillus salivarius UCC118Bac+ (producing bacteriocin) or the bacteriocin-negative strain L. salivarius UCC118Bac− (non-bacteriocin-producing) to rats can modulate the gut microbiota [99]. However, only the bacteriocin-producing probiotics increased the number of Bacteroidetes and Proteobacteria and decreased the number of Actinobacteria compared with the non-bacteriocin-producing control treatments.…”
Section: Discussionmentioning
confidence: 99%
“…As a potential probiotic, Lactobacillus salivarius ( L. salivarius ) exhibits inhibitory effects on intestinal pathogens and regulates the equilibrium of the gut microbiome by producing various metabolites, antibacterial compounds, antioxidants, and organic acids [ 1 , 2 ]. L. salivarius is also reported to alleviate diseases of the liver by reshaping the gut microbiota, regulating lipid metabolism and inflammation, and promoting lipid degradation [ 3 - 5 ].…”
Section: Introductionmentioning
confidence: 99%